Restorative Justice and Anti-Corruption Law: Toward a Progressive Penal Policy in Indonesia - Putri, Nabilah Talithania Azaria; Ratnasari, Ayu; Firananda, Givana Adhitya (UIN Sunan Kalijaga Yogyakarta, 2024)
The eradication of corruption in Indonesia, as regulated by Law Number 31 of 1999 on the Eradication of Corruption Crimes, remains predominantly oriented toward retributive sanctions. In contrast, the new Indonesian Criminal Code (KUHP) introduces a progressive and participatory penal policy paradigm by incorporating Restorative Justice (RJ) to restore victims' losses and strengthen social balance. This divergence in orientation creates potential ambiguity in law enforcement, particularly regarding the scope and criteria for applying RJ to corruption, which has long been categorized as a crime against the public interest. Previous studies have mainly concentrated on the effectiveness of punitive sanctions, leaving limited scholarly attention to the normative dimensions of RJ's integration into anti-corruption law and its compatibility with international regimes such as the United Nations Convention against Corruption (UNCAC), asset recovery mechanisms, civil recovery, non-conviction-based confiscation, and deferred prosecution agreements. This study aims to fill that gap by offering a normative framework harmonizing restorative justice principles with anti-corruption enforcement. Employing normative juridical research with a statute approach and a conceptual approach, this paper highlights the potential of RJ to complement punitive measures, enhance asset recovery, and align national law with global standards. This research contributes to proposing a more coherent and integrated anti-corruption penal policy that balances deterrence with restorative outcomes. In doing so, it enriches the academic discourse on Indonesia's criminal law reform. It provides a conceptual foundation for policymakers to design a corruption eradication regime that is consistent, effective, and internationally compatible.